2016
DOI: 10.1007/s00408-016-9939-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Vitamin D: A Novel Strategy to Enhance Neonatal Lung Maturation

Abstract: Introduction The physiologic vitamin D (VD), 1α,25(OH)2 D3 (1,25D) is a local paracrine/autocrine effecter of fetal lung maturation. By stimulating alveolar type II cell and lipofibroblast proliferation and differentiation, parenterally administered 1,25D has been shown to enhance neonatal lung maturation; but due to the potential systemic side effects of the parenteral route, the translational value of these findings might be limited. To minimize the possibility of systemic toxicity, we examined the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Other in vivo studies support the role of vitamin D in pulmonary function. Taylor, et al, showed promising and provocative results utilizing a neonatal rat model ( 41 ). The investigators randomized one-day-old rat pups to one of three different doses of the active hormone, 1,25(OH)D 2 and its physiologic precursor 25(OH)D, or the diluent, via nebulization daily for 14 days.…”
Section: Relevant Data Surrounding Vitamin D Deficiency During Pregnamentioning
confidence: 99%
“…Other in vivo studies support the role of vitamin D in pulmonary function. Taylor, et al, showed promising and provocative results utilizing a neonatal rat model ( 41 ). The investigators randomized one-day-old rat pups to one of three different doses of the active hormone, 1,25(OH)D 2 and its physiologic precursor 25(OH)D, or the diluent, via nebulization daily for 14 days.…”
Section: Relevant Data Surrounding Vitamin D Deficiency During Pregnamentioning
confidence: 99%
“…Vitamin D has also effects on lung development and function. Experimental and human studies have revealed vitamin D to play a key role in lung maturation by modulating type II alveolar cell differentiation and by stimulating surfactant synthesis and release . Antenatal vitamin D deficiency impairs airway and alveolar development and limits lung function in mice .…”
Section: Possible Explanations Of Findingsmentioning
confidence: 99%
“…Experimental and human studies have revealed vitamin D to play a key role in lung maturation by modulating type II alveolar cell differentiation and by stimulating surfactant synthesis and release. [62][63][64][65] Antenatal vitamin D deficiency impairs airway and alveolar development and limits lung function in mice. 9 Moreover, vitamin D deficiency may provoke proliferation and hypertrophy of smooth muscle, contributing to airway remodeling and increased airway smooth muscle mass.…”
Section: P Oss Ib Le E Xpl Anati On S Of Finding Smentioning
confidence: 99%
“…In addition, calcitriol supplementation during lactation in rodents with previous deficiency during gestation improves alveolar septation and lung function [95]. Even in pups from normal pregnant rats, the aerosol administration of calcitriol precursors contributes to lung maturity by increasing the expression of markers of epithelial, mesenchymal, and vascular differentiation that is followed by an increase in the synthesis of surfactant phospholipids [96]. In human studies, there is an association between a reduction of calcitriol levels in 18 WG and a reduced lung function in childhood [97].…”
Section: Cholecalciferolmentioning
confidence: 99%
“…Formation of bronchial tubules during pseudoglandular phase [57] Lung maturation [62,69,70,72,[77][78][79] In vitro Proliferation of ATII cells and differentiation to ATI cells [62,81] In vitro and in vivo SFTPs expression [62,63] Cholecalciferol Branching morphogenesis [91] In vitro proliferation of ATII cells [96] In vitro surfactant phospholipids secretion [96] In vitro SFTPs expression [96] Lung maturation [95,96] Abbreviations Funding: This research received no external funding.…”
Section: Hormone Action In Lung Development Referencesmentioning
confidence: 99%